Are Public Investment and Education Expenditures Productive in the Argentine Case? A FMOLS and DOLS Analysis, 1960-2019 - Ramirez, Miguel D. (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This paper examines whether public investment spending and public education expenditures (a proxy for human capital) in Argentina have a positive and significant effect on economic output and labor productivity for the 1960-2019 period. The paper estimates a simple model that incorporates the impact of public and private investment spending, education expenditures (including at the secondary level), and the labor force. It presents a modified empirical counterpart to the simple model and tests for unit roots and performs both a Johansen cointegration test and a Gregory and Hansen cointegration test with an endogenously determined regime shift. FMOLS and DOLS long-run estimates for the 1960-2019 period suggest that public and private investment spending, government education expenditures, and the labor force have a positive and significant effect on the level of economic output and labor productivity. For comparison purposes, both methodologies are used because these estimators are extremely consistent, particularly the DOLS estimator, even in the presence of both endogeneity and serial correlation of any order. The concluding section summarizes the major results and discusses potential avenues for future research on this important topic.